Conceptual Distinction between Shariah Governance and Corporate Governance in Islamic Finance - Prasojo Prasojo (INSTITUT AGAMA ISLAM SEBI, 2026)
This article examines the conceptual differences between corporate governance and sharia governance by comparing their roles and oversight functions. The analysis is based on a critical synthesis of governance theory, agency theory, and the Islamic finance governance literature. The results show that corporate governance and sharia governance address different dimensions of risk. Corporate governance focuses on financial discipline and managerial oversight. Meanwhile, Sharia governance focuses on validating contractual compliance and adherence to Sharia principles. Therefore, the proposed conceptual framework positions financial approval and Sharia validation as two sequential phases of oversight. The framework illustrates the relationship between the two governance systems, provides a theoretical foundation for further empirical research, and serves as a reference for regulators and Islamic financial institutions in designing stronger governance structures to enhance accountability. Existing empirical literature still views Shariah governance as part of corporate governance. This implies a need to strengthen the theoretical foundation and support the formation of a more integrated governance structure within Islamic financial institutions.